1990
DOI: 10.1159/000185892
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Renal Graft due to Recurrent IgA Nephropathy with Rapidly Progressive Course: An Unusual Clinical Evolution

Abstract: Recurrence of IgA nephropathy following renal transplantation has been described in 40–50% of patients, and it usually has a good outcome. We present the case of a 54-year-old man wiht IgA nephropathy who developed terminal renal failure in 1985,3 years after the onset of the disease. In March 1986 he received a cadaveric renal allograft following treatment with ciclosporin and steroids. Eight months later he developed microhaematuria and proteinuria and 10 months later he developed acute nephritic syndrome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 5 publications
0
19
1
Order By: Relevance
“…These patients with recurrent IgA nephropathy often presented crescent formation in histology with rapidly progressive renal failure. [9][10][11][12] In this study, we found that our patients had no response or just short time response to intensive immunosuppressive therapy. All of our patients changed their initial immunosuppressive regimens; however, six advanced to renal graft loss within 2 to 12 months, three of them eventually developed ESRD and returned to hemodialysis therapy within two years after kidney transplantation, and only one kept stable graft function for more than three years of follow-up.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These patients with recurrent IgA nephropathy often presented crescent formation in histology with rapidly progressive renal failure. [9][10][11][12] In this study, we found that our patients had no response or just short time response to intensive immunosuppressive therapy. All of our patients changed their initial immunosuppressive regimens; however, six advanced to renal graft loss within 2 to 12 months, three of them eventually developed ESRD and returned to hemodialysis therapy within two years after kidney transplantation, and only one kept stable graft function for more than three years of follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…[9][10][11][12] We reported 10 cases that were diagnosed as recurrent or de novo IgA nephropathy with crescent formation. They aged from 25 to 65 years old, and 80% were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these lost his graft from recurrent IgA nephropathy, but not with an acute cres centic course. Further attention as drawn to the possibility of clinically important recur rence by Diaz-Tejeiro et al [2] and despite an initial honeymoon period after plasma ex change and cyclophosphamide treatment, the graft was lost 5 months later. In the patient we have described, the acute glomerulonephritis appeared to have started to resolve prior to the initiation of plasma exchange, so no addi…”
Section: Case Reportmentioning
confidence: 99%
“…Recurrence rates of 38-50% have been described in different mor phological series [1][2][3]. However, there is general agreement that it is rare for such histo logical disease to be clinically important [4.5], Diaz-Tejeiro et al [2] reported a case of recur rent IgA nephropathy having a rapidly pro gressive course and proceeding to graft loss. We report a second case of crescentic IgA nephropathy in a renal allograft and suggest that this complication may not be as unusual as originally thought.…”
mentioning
confidence: 99%